Review of Jan Doolittle Wilson’s Becoming Disabled: Forging a Disability View of the World, In Becoming Disabled: Forging a Disability of the World (Lexington Books, 2021) - Monika Shehi Herr (Qualitative Research in Medicine & Healthcare)
Jan Doolittle Wilson doesn’t invite as much as she compels the readers to do the uncomfortable, complicated, and necessary work of reimagining disability. Writing not only as a scholar of disability studies, but also as a disabled person, the granddaughter of a disabled woman, and the mother of a disabled child, Wilson uses an autoethnographic approach to not only get able-bodied readers to see disabled people in a new light, but also, and above all, to turn their gaze towards themselves and question their own understanding of disability. As Wilson explains, the autoethnographic approach is “defined as one in which an author draws on personal experiences to analyze and create meaning about larger social, cultural, and political phenomena” (p. 6). [...]